Imagining the Nation on the Screen: The Poetics of Palestinian Cinema’s Fourth Period - Ben-Zvi Morad, Yael (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
This article explores Palestinian cinema’s fourth period of activity that began around 1980. During this time, the world did not acknowledge the existence of the Palestinian people and their territory. Palestinian cinema thus emerged as a tool to create a national identity and voice, and to establish a continuous time and space that defined their history and territory. The films projected a collective consciousness that united the dispersed Palestinian community, creating a shared community. To achieve these goals, Palestinian cinema employed unique and complex artistic means, with its national purpose remaining consistent with its complex cinematic poetics. This bird’s-eye-view article highlights the shared spirit of the films and emphasizes the commonality beyond the differences. It offers an insight into the cinematic language that characterized this period and the principles that made Palestinian cinema a unique voice on the global stage.